The Construction of the Genetic Order: A Short Critical History - Papillon, Daniel (Organisms. Journal of Biological Sciences, 2021)
Genetics, as all human activities, is a situated practice. Given its enormous cultural and epistemological influence, the young age of the discipline may be surprising - not even 150 years old. The creation of the science of the heredity and production of traits in organisms responded to 19th century’s epistemological needs in biology, as well as political and social developments: the transmission of characters and their variations throughout generations needed a new theory, the embryological development of organisms had to be explained, the unrest and disastrous living conditions provoked by the industrial capitalism and the colonial project in the West called for a reaction from the elites. The trajectory of genetics is one of permanent co-production between the different ontologies and practices it is situated in. As a science, it draws its legitimacy from the stories it tells (about the world or about itself), the interests it serves and the existing power relations it is part of. Given this background, the present work tries to shed some light on several aspects of the history of genetics that may help clarify its role and impact on our societies. The set of ontological and material transformations it underpins is referred to as the Genetic Order, and this is explored particularly in the context of the irremediable past and present association of genetics with eugenics, the construction of key notions such as heritability and the dichotomy Nature/Nurture, the enormous influence of cybernetics over biology and genetics after the second world war and the alliance between biotechnologies, genetics and neoliberalism in more recent years. One key notion that wanders throughout this text is that of control, over bodies and life in general. This is illustrated by the recent explosion of the genomic prediction industry and its impact on contemporary subjectivities. In the end, it is a world of statistics, algorithms, predestination, risk management and control that the Genetic Order offers, echoing the hegemonic influence of the neoliberal cybernetic project where all that lives must be engineered, modelled, monitored, predictable and transparent.